Hospital Volumes of Inpatient Pediatric Surgery in the United States. (11th October 2021) - Berry, Jay G.; Rodean, Jonathan; Leahy, Izabela; Rangel, Shawn; Johnson, Connor; Crofton, Charis; Staffa, Steven J.; Hall, Matt; Methot, Craig; Desmarais, Anna; Ferrari, Lynne
Abstract : BACKGROUND: Perioperative outcomes of children depend on the skill and expertise in managing pediatric patients, as well as integration of surgical, anesthesiology, and medical teams. We compared the types of pediatric patients and inpatient surgical procedures performed in low- versus higher-volume hospitals throughout the United States. METHODS: Retrospective analysis of 323, 258 hospitalizations with an operation for children age 0 to 17 years in 2857 hospitals included in the Agency for Healthcare Research and Quality (AHRQ) Kids' Inpatient Database (KID) 2016. Hospitals were categorized by their volume of annual inpatient surgical procedures. Specific surgeries were distinguished with the AHRQ Clinical Classification System. We assessed complex chronic conditions (CCCs) using Feudtner and Colleagues' system. RESULTS: The median annual volume of pediatric inpatient surgeries across US hospitals was 8 (interquartile range [IQR], 3–29). The median volume of inpatient surgeries for children with a CCC was 4 (IQR, 1–13). Low-volume hospitals performed significantly fewer types of surgeries (median 2 vs 131 types of surgeries in hospitals with 1–24 vs ≥2000 volumes). Appendectomy and fixation of bone fracture were among the most common surgeries in low-volume hospitals. As the volume of surgical procedures increased from 1 to 24 to ≥2000, the percentage of older children ages 11 to 17 years decreased (70.9%–32.0% [ P < .001]) and the percentage of children with a CCC increased (11.2%–60.0% [ P < .001]). CONCLUSIONS: Thousands of US hospitals performed inpatient surgeries on few pediatric patients, including those with CCCs who have the highest risk of perioperative morbidity and mortality. Evaluation of perioperative decision making, workflows, and pediatric clinicians in low- and higher-volume hospitals is warranted.